POLYMORPHIC SSR MARKERS AMONG ORYZA SATIVA CV. SWARNA AND ITS DERIVED ADVANCED BACKCROSS LINES WITH WILD INTROGRESSIONS FROM O. NIVARA - AND D. SRINIVASA CHARY, N.P.S. DE SILVA, B. KAVITHA (The Journal of Research, PJTSAU, 2021)
Wild species derived introgression lines are good source of novel genes for improving complex traits like yield. Identification of molecular markers revealing genotypic polymorphism is a prerequisite for mapping QTLs and genes for target traits. Polymorphism between parental lines of mapping populations involving Swarna, 166s and 148s was identified in this study. Swarna is a high yielding mega variety, while, 166s and 148s are advanced backcross introgression lines (BILs) developed from a cross between Swarna x O. nivara. A total of 530 randomly selected SSR markers were used to identify the polymorphism between Swarna and BILs 166s and 148s. Eighty eight markers (16.66%) which showed distinct alleles between Swarna and 166s were again used to study the polymorphism between Swarna/148s and 166s/148s. Out of 88 markers, 50 were (56.81%) polymorphic between Swarna/148s and 54 markers (61.36%) were polymorphic between 166s /148s. Some of these polymorphic SSR markers were already reported as linked to yield traits in previous studies. These identified markers will be useful in further QTL mapping of the populations derived from the parental lines used in this study.